(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. Gentamicin sulphate nephrotoxicity seems to be attributed to the generation of reactive oxygen species. Olive leaf extract (OLE) has been demonstrated to have antioxidant and anti-inflammatory effects. The aim of this study was to evaluate the inhibitory effect of OLE on gentamicin-induced nephrotoxicity in rats. Materials and Methods. Thirty-five Sprague-dawley rats were divided into 5 groups to receive saline; gentamicin, 100 mg/kg/d; and gentamicin plus OLE in 3 different doses (25 mg/kg/d, 50 mg/kg/d, and 100 mg/kg/d, once daily for 12 days. Serum and renal malondialdehyde were assessed, and tubular necrosis was studied semiquantitatively. Glomerular volume and volume density of the proximal convoluted tubules were estimated stereologically from paraffin sections. Serum creatinine and renal antioxidant enzymes activity were measured. Results. Gentamicin significantly increased serum creatinine, malondialdehyde, and tubular necrosis, and decreased creatinine clearance, volume density of the proximal convoluted tubules, renal glutathione, glutathione peroxidase, catalase, and superoxide dismutase compared with the control group. Cotreatment of gentamicin and OLE significantly decreased serum creatinine, malondialdehyde, tubular necrosis, and renal malondialdehyde, and increased renal glutathione, catalase, superoxide dismutase, volume density of proximal convoluted tubules, and creatinine clearance in comparison with gentamicin-only treated group. Serum malondialdehyde, serum creatinine, tubular necrosis, and volume density of proximal convoluted tubules were maintained at the same level as that of the control group by cotreatment of gentamicin and OLE. Conclusions. Olive leaf extract ameliorates gentamicin nephrotoxicity via antioxidant activity, increase of renal glutathione content, and increase of renal antioxidant enzymes activity, except for glutathione peroxidase.